2018
DOI: 10.1096/fj.201801086rr
|View full text |Cite
|
Sign up to set email alerts
|

Role of TLR4‐MAP4K4 signaling pathway in models of oxygen‐induced retinopathy

Abstract: Retinopathy of prematurity is a vision‐threatening condition, and therapies based on antagonizing VEGF may elicit serious side effects in premature infants. Mechanisms of retinal angiogenesis, particularly the signaling pathways independent of VEGF, remain elusive. The goals of our study were to explore TLR4‐mediated signaling pathways in human retinal microvascular endothelial cells (HRMECs) and to examine the effects of TLR4 antagonists in models of oxygen‐induced retinopathy (OIR). Our results show that int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…TLR members play an important role in recognizing pathogen-associated molecular patterns and are crucial components in the innate immunity (31). Earlier studies have shown that the interaction between TLRs and myeloid differentiation protein 88 further activates MAPK p38, JNK, and NF-kB, which is essential to produce cytokines such as IL IL-6, IL-8, and TNF-a (32).…”
Section: Discussionmentioning
confidence: 99%
“…TLR members play an important role in recognizing pathogen-associated molecular patterns and are crucial components in the innate immunity (31). Earlier studies have shown that the interaction between TLRs and myeloid differentiation protein 88 further activates MAPK p38, JNK, and NF-kB, which is essential to produce cytokines such as IL IL-6, IL-8, and TNF-a (32).…”
Section: Discussionmentioning
confidence: 99%
“…This is a reasonable result because the structure of ranibizumab is similar to that of bevacizumab Fab, which lacks the ability to interact with mouse VEGF. 29,30 Since there are many articles about the use of ranibizumab as an effective anti-VEGF drug in mice, [17][18][19][20][21][22][23] we believe it is necessary to alert ophthalmology researchers against using ranibizumab as an anti-VEGF drug in the future mouse experiments.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why ranibizumab showed anti-VEGF effects in previous reports, [17][18][19][20][21][22] but we suspect that the use of poor quantitative methods such as uorescein angiography, 19 immunostaining of retinal sections, [18][19][20] or uorescein isothiocyanate (FITC)-dextran perfused retinal at mounts 18,20 may have led to different results. Fluorescein angiography is suitable for qualitative analysis, but not quantitative analysis because the amount of ash light and the timing of the photography after uorescein injection may cause the results to vary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TLR4 levels are raised in response to retinal IR injury (13,140,142,(146)(147)(148)(149) and hypoxia (7,150). In particular, TLR4 levels are highly expressed in the INL (13,146) and GCL (13,142,146) following I/R injury.…”
Section: Inflammatory Pathwaysmentioning
confidence: 99%